107 Results through relationships: developing core capabilities in end of life care. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Dorman, Saskie; Rogers, Adrienne; Macdonald, Fiona; Howard, Sarah; Brogan, Andy
Abstract : Background: There are numerous performance indicators in end of life care, including those used by health and social care regulators. This can make it hard to focus on what really matters. As part of our system-wide work to improve personalised care and support towards the end of life, we focused on core capabilities. What do we need to be really good at, consistently, to make sure that everyone has as good an experience as possible in their last year of life? Methods: We used the clean framework – 'clean in, clean through, clean out' – establishing sound beginnings, middle and endings – to create a list of capabilities. We refined these iteratively, focusing on elements which are necessary and sufficient. The core capabilities were validated with stakeholders including people and their families, health and social care clinical and managerial staff. Results: Our core capabilities are: We recognise when you may be in the last months of your life. We all understand what really matters to you and your family, and focus on this together. You are supported to live well in your own way, as part of your community, finding moments of joy where possible. You are supported to anticipate what may happen towards the end of your life. Your wishes are shared as appropriate (with your consent) so that you are supported through times of illness in a way which feels right to you. You are as comfortable as you want to be, including in the last days of your life. Those close to you feel supported, including after your death. Conclusion: The clean framework offers a useful way to structure core capabilities, which can be used to focus on what really matters both in everyday practice and in organisational review of end of life care.